Socio-Cultural Code as a Factor of Unity and Variability of Generations - Sadykova, Hadia Nurgalievna; Khairullina, Nursafa Gafurovna; Ustinova, Oksana Vyacheslavovna; Pelkova, Svetlana Vladimirovna; Efremova, Tatyana Michailovna (International Journal of Economics and Financial Issues, 2015)
This paper examines the problem of the formation of value orientations and cultural continuity between the generations in the modern conditions of Russian society on the results of a questionnaire survey conducted in 2013-2014. in Tyumen and in the south of the Tyumen 700 people aged 15 years. In the analysis it was identified generational groups such as the generation of the Soviet era (51 and older) - generation of «S» (Soviet); perestroika generation (31-50 years) - Generation «P» (Perestroika); post-perestroika generation (18-30 years) - Generation «PP»; transitive generation (15-17 years) - generation of «E» (Eve). This has allowed to characterize: the perception and assessment of the socio-economic situation; dominant values (revealing aspects of connecting or separating intergenerational interaction); the basic necessities of life (setup man to the regeneration of the system of values, as a response to external transformation); social interaction: the frequency of contact and distress inside generational group and outside it; social interaction: the frequency of contact and distress inside generational group and outside it; strategic goals (design their own future in the qualitative and quantitative parameters allows to characterize the dynamics of social processes and build a model of effective collaboration, allowing to neutralize the existing negative trends and promote the formation and functioning of the automatic controllers that support progressive social development). Keywords: generation, values, socio-cultural code, social interaction, generational approach, intergenerational cultural transmission JEL Classification: Ð13